2006
DOI: 10.1111/j.1462-2920.2006.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fimbrial gene clusters and their expression in enterohaemorrhagic Escherichia coli O157:H7

Abstract: The sequence of two enterohaemorrhagic Escherichia coli (EHEC) O157:H7 strains reveals the possession of at least 16 fimbrial gene clusters, many of the chaperone/usher class. The first part of this study examined the distribution of these clusters in a selection of EHEC/EPEC (enteropathogenic E. coli) serotypes to determine if any were likely to be unique to E. coli O157:H7. Six of the clusters, as determined by the presence of amplified main subunit or usher gene sequences, were detected only in the E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 56 publications
6
133
1
Order By: Relevance
“…It is likely that in some E. coli strains, hcpA gene expression, like that of many other virulence factors, requires specific growth conditions that trigger or repress regulatory elements that lead to successful gene expression. So far, the HCP has been observed only in E. coli O157:H7, and other studies have indicated that hcpA is a cryptic gene in laboratory and pathogenic strains (14,26,49). While the hcpA gene is widely distributed among E. coli strains, it remains unknown what E. coli pathogroups apart from EHEC assemble HCP.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that in some E. coli strains, hcpA gene expression, like that of many other virulence factors, requires specific growth conditions that trigger or repress regulatory elements that lead to successful gene expression. So far, the HCP has been observed only in E. coli O157:H7, and other studies have indicated that hcpA is a cryptic gene in laboratory and pathogenic strains (14,26,49). While the hcpA gene is widely distributed among E. coli strains, it remains unknown what E. coli pathogroups apart from EHEC assemble HCP.…”
Section: Discussionmentioning
confidence: 99%
“…Except for genes encoding curli (csgA), a fimA-like gene, and ybgD and yehD (putative pilin genes), the expression of the remaining 12 pilin subunit genes, including ecpA, was not demonstrated under the conditions examined (32). Likewise, genome-wide-scale efforts using transposon or signature-tagged mutagenesis have not evidenced a role for ECP in adherence to Caco-2 cells or in colonization of the bovine gastrointestinal tract (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the 16 putative pili operons present in EHEC O157:H7 was previously investigated through transcriptional analysis (32). Except for genes encoding curli (csgA), a fimA-like gene, and ybgD and yehD (putative pilin genes), the expression of the remaining 12 pilin subunit genes, including ecpA, was not demonstrated under the conditions examined (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of E. coli O157:H7 contains 16 loci encoding genes putatively involved in fimbriae or pili biosynthesis (26)(27)(28), but it is unknown how many of them are functional in vivo. Several fimbriae have been identified in EHEC strains, including the sorbitolfermenting EHEC O157 fimbriae plasmid-encoded (SFP) (29), 2 loci-encoding long polar fimbriae (30), curli (31), F9 (a type I pilus homolog) (32), and a type IV pilus (TFP) in LEE-negative non-O157: H7 STEC (33).…”
Section: Introductionmentioning
confidence: 99%